Peripheral Visual Reaction Time Is Faster in Deaf Adults and British Sign Language Interpreters than in Hearing Adults - Codina, Charlotte J.; Pascalis, Olivier; Baseler, Heidi A.; Levine, Alexandra T.; Buckley, David (Frontiers in Psychology, 2017)
Following auditory deprivation, the remaining sense of vision has shown selective enhancement in visual cognition, especially in the area of near peripheral vision. Visual acuity is poor in the far periphery and may be an area where sound confers the greatest advantage in hearing persons. Experience with a visuospatial language such as British Sign Language (BSL) makes additional demands on the visual system. To test the different and separable effects of deafness and use of a visuo-spatial language on far peripheral visual processing, we investigated visual reaction times (RTs) and response accuracy to visual stimuli, between 30° and 85° along the four cardinal and four inter-cardinal meridians. We used three luminances of static, briefly illuminated stimuli in visually normal adults. The cohort tested included profoundly congenitally deaf adults (N=17), hearing fluent BSL users (N=8) and hearing non-signing adults (N = 18). All participants were tested using a peripheral forced choice paradigm designed previously to test deaf and hearing children (Codina et al, 2011a). Deaf adults demonstrated significantly faster RTs to all far peripheral stimuli and exceeded the abilities of both signing and non-signing hearing adults. Deaf adults were significantly faster than BSL interpreters, who in turn were significantly faster than hearing non-signing adults. The differences in RT demonstrated between groups were consistent across all visual field meridia and were not localised to any one region of the visual field. There were no differences found between any groups in accuracy of detecting these static stimuli at any retinal location. Early onset auditory deprivation appears to lead to a response time visual advantage in far peripheral responses to briefly presented, static LED stimuli, especially in the right visual field. Fluency in BSL facilitates faster visuo-motor responses in the peripheral visual field, but to a lesser extent than congenital, profound deafness.